2002
DOI: 10.1038/sj.onc.1205972
|View full text |Cite
|
Sign up to set email alerts
|

Aplidin™ induces the mitochondrial apoptotic pathway via oxidative stress-mediated JNK and p38 activation and protein kinase C δ

Abstract: AplidinTM , a new antitumoural drug presently in phase II clinical trials, has shown both in vitro and in vivo activity against human cancer cells. Aplidin TM effectively inhibits cell viability by triggering a canonical apoptotic program resulting in alterations in cell morphology, caspase activation, and chromatin fragmentation. Pro-apoptotic concentrations of Aplidin TM induce early oxidative stress, which results in a rapid and persistent activation of both JNK and p38 MAPK and a biphasic activation of ERK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
106
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 66 publications
5
106
1
Order By: Relevance
“…In All-PO cells at 72 h after drug-washout 80% of the cells treated with 20 nM of Aplidin were apoptotic. As previously reported on other cell type (Garcia-Fernandez et al, 2002), Aplidin was found to induce apoptosis in a caspase-3-dependent manner ( Figure 5). …”
Section: Aplidin-induced Apoptosis On All Cell Linessupporting
confidence: 88%
“…In All-PO cells at 72 h after drug-washout 80% of the cells treated with 20 nM of Aplidin were apoptotic. As previously reported on other cell type (Garcia-Fernandez et al, 2002), Aplidin was found to induce apoptosis in a caspase-3-dependent manner ( Figure 5). …”
Section: Aplidin-induced Apoptosis On All Cell Linessupporting
confidence: 88%
“…In the subsequent studies, the mitochondrial changes were shown to be caused by different interactions. The sustained activation and phosporylation of c-Jun N-terminal kinase (JNK) by reactive oxygen species (ROS) is recognised as one of the crucial mechanisms in the effects of Aplidin on breast cancer cells (Garcia-Fernandez et al, 2002;Cuadrado et al, 2004;GonzalezSantiago et al, 2006;Suarez et al, 2006). This ROS induction was found to be caused by an alteration in the glutathione homeostasis and by a rapid activation of the small GTP-binding protein Rac (Cuadrado et al, 2003;Gonzalez-Santiago et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving the mechanism of action of Aplidin indicate that this compound acts through a complex number of events that affect proliferation, cell-cycle progression and apoptosis (Erba et al, 2002;Garcia-Fernandez et al, 2002). In 5T33MMvt cells, Aplidin induces a G0/G1 cell-cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 On the other hand, rapid posttranscriptionally mediated up-regulation of eEF1A has been demonstrated following oxidative stress-induced apoptosis (e.g., upon treatment with hydrogen peroxide). 53 Remarkably, apoptosis induced by dehydrodidemnin has been shown to involve generation of oxidative stress, which can be largely prevented by the glutathione peroxidase mimetic ebselen, 54 and the very weak apoptotic response that is evoked in human normal peripheral blood lymphocytes by this agent (100 nM for 24 h) has been shown to be greatly enhanced in leukemic cells or mitogen-stimulated T-lymphocytes. 55 Since overexpression of eEF1A results in selective resistance to apoptosis induced by growth factor withdrawal and endoplasmic reticulum stress, but not from nuclear damage or death receptor signaling, 56 a global pivotal role of eEF1A levels in the modulation of apoptosis rate has been suggested.…”
Section: Discussionmentioning
confidence: 99%